Wireless Network Channel Interference for Mobile Communication: a Systematic Literature Review and Research Agenda - Mujahidin, Irfan; Putra, Ivandi Julatha (JAICT, 2023)
The development and renewal of wireless technology is currently a necessity. Wifi technology has now reached wifi 6. Network infrastructure is currently the main thing in the process of distributing data using wireless media to mobile phone or laptop users. By looking at the need for wireless in offices, schools, public places, hospitals, and indoor or outdoor buildings that use a large number of access point devices. Based on a review of existing research obtained problems and opportunities for development, this literature study taken from 25 journal articles aims to be able to plan the construction of wireless network infrastructure so that channel interference does not occur. Research on wireless network channel interference has been carried out in several scenarios, for example, by increasing the number of wireless networks in adjacent areas, providing obstacles, and managing different channels. The eight most common methods used in wireless network channel interference research are descriptive analysis, comparative study, method analysis, model development, case studies, regression models, literature studies, and optimization. Research related to wireless network channel interference can still be further developed by using the latest wireless technology which can simultaneously test existing channel interference